Dukungan Keluarga Terhadap Kepatuhan Minum Obat Penderita Malaria - Njakatara, Umbu Nggiku; Kareri Hara, Maria; Landi, Melkisedek (JURNAL KESEHATAN PRIMER, 2021)
Background:  Malaria is a persistent public health issue caused by the Plasmodium parasite and transmitted by female Anopheles mosquitoes. Treatment aims to eradicate the parasite in all stages, curing patients and breaking transmission. The Indonesian government is working toward a malaria-free target by 2030, reducing Annual Parasite Incidence (API). Vector control efforts include indoor spraying, insecticide-treated nets, larvicides, and modifying mosquito breeding habitats. Objective: To determine the relationship between family support and medication adherence for malaria sufferers. Method: This research is a descriptive quantitative research with a research design using a sectional design. The number of samples used was 30 respondents using purposive sampling with survey techniques. Data were analyzed univariately and bivariately on the characteristics of respondents and the relationship between the two research variables using the Spearman-Rho test. Results: The results of the study showed that there was a significant relationship between family support and Malaria patients' compliance in taking Malaria medication.